Evaluative state, nation-state: a last hurrah? (Revista Lusófona de Educação, 2018)
The paper takes a resolutely historical and political perspective in analysing the rise of the Evaluative State in its European setting. He traces the development of four versions of the Evaluative State from its origins in the mid to late Eighties in terms of two stages: first, its operational purpose, second, its subsequent re-definition of ownership and role in steering higher education policy. Focusing primarily on the three pioneering systems - France, the United Kingdom, the Netherlands and later Portugal, the author argues that the present dynamic of the Evaluative State marks a major step in the history of higher education policy. If today the Evaluative State acts as the prime instrument of economic Liberalism as the common basis of European higher education policy, its purpose in the original setting of Nation-State was very different. Such differences are examined, and the impact of the Evaluative State weighed up in its various forms.Keywords: evaluative State; higher education policy; system steering; policy control and the nation-state.